Feedback during learning gymnastic exercises - Niznikowski, T. (Theory and Practice of Physical Culture, 2020)
Objective: Studying the impact of two different types of verbal cues in the process of teaching complex gymnastic exercises - double salto backward piked to dismount from uneven bars.